Size of silk fibroin β-sheet domains affected by Ca2+. Issue 40 (4th October 2016) - Drnovšek, N.; Kocen, R.; Gantar, A.; Drobnič-Košorok, M.; Leonardi, A.; Križaj, I.; Rečnik, A.; Novak, S.
Abstract : Addition of bioactive glass or other Ca 2+ source to fibroin changes scaffold degradation and the mechanical and protein secondary structure properties due to the reduction in the size of β-sheet domains. Abstract : In the search for suitable scaffold materials for tissue regeneration, silk fibroin has become one of the most promising candidates due to its biocompatibility and good physical properties. To facilitate bone formation in osteochondral defects, it is often combined with a bone promoting additive. Here we demonstrate using HRTEM analysis how the release of Ca 2+ ions from bioactive glass or Ca-salts results in the reduction of β-sheet domain size that effectively controls a scaffold's properties, such as degradation and mechanical stiffness. We show that these changes already occur in silk fibroin solution prior to scaffold preparation and are caused by a decrease in zeta potential that forces fibroin molecules into tighter packing resulting in higher scaffold crystallinity, smaller β-sheet domains and higher interconnectivity. The reduction of β-sheet domains improves the elastic modulus and allows faster degradation despite the higher crystallinity. Ca 2+ was also shown to be beneficial to the formation of hydroxy-apatite sheets on the fibroin surface.